Costly lifetime maternal investment in killer whales - Weiss, MN; Ellis, S; Franks, DW; Nielsen, MLK; Cant, MA; Johnstone, RA; Ellifrit, DK; Balcomb, KC; Croft, DP (Current Biology, 2022)
This is the final version. Available on open access from Cell Press via the DOI in this record Data and code availability All data and code necessary to replicate analyses in this study have been deposited on Zenodo (DOI:10.5281/zenodo.7457806). Parents often sacrifice their own future reproductive success to boost the survival of their offspring, a phenomenon referred to as parental investment. In several social mammals, mothers continue to improve the survival of their offspring well into adulthood, however whether this extended care comes at a reproductive costs to mothers, and therefore represents maternal investment, is not well understood. We tested whether lifetime maternal care is a form of parental investment in fish-eating “resident” killer whales. Adult killer whales, particularly males, are known to receive survival benefits from their mothers, however whether this comes at a cost to mothers’ reproductive success is not known. Using multiple decades of complete census data from the “southern resident” population, we found a strong negative correlation between females’ number of surviving weaned sons and their annual probability of producing a viable calf. This negative effect did not attenuate as sons grew older, and the cost of sons could not be explained by long-term costs of lactation or group composition effects, supporting the hypothesis that caring for adult sons is reproductively costly. This is the first direct evidence of lifetime maternal investment in an iteroparous animal, revealing a previously unknown life history strategy. Natural Environment Research Council (NERC) Leverhulme Trust